Correlation between the variation of the ionizing continuum and broad absorption lines. (26th October 2017) - Lu, Wei-Jian; Lin, Ying-Ru; Qin, Yi-Ping
Abstract: In this Letter, we present an analysis of the relation between the variability of broad absorption lines (BALs) and that of the continuum. Our sample is multi-epoch observations of 483 quasars by the Sloan Digital Sky Survey-I/II/III (SDSS-I/II/III). We derive the fractional flux variations of the continuum and fractional equivalent width (EW) variations for C iv and Si iv BALs, and explore the correlations between the three. Our results reveal moderate anticorrelations with high significance level between the fractional flux variations of the continuum and fractional EW variations for both C iv and Si iv BALs. We also prove a significant positive correlation between the fractional EW variations for C iv and Si iv BALs, which is in agreement with several previous studies. Our discoveries can serve as evidence for the idea: Change of an ionizing continuum is the primary driver of BAL variability.